RANCANG BANGUN PROTOTYPE INTELLIGENT BOOTH KAKI LIMA (OTOMATISASI BUKA/TUTUP) - Thomas Thomas; Wawan Nurmansyah (Jurnal Ilmiah Matrik, 2019)
A food and beverage booth owner who sells alongside the road, has difficulty when opening and closing the booth also when the rain comes suddenly - suddenly the owner has difficulty protecting electronic equipment from rainwater which can cause a short circuit, because the process is still done manually. To overcome this problem, a system with a microcontroller circuit using Arduino Uno and a DC motor can be made that can open and close the booth with a push button command that can facilitate the process which is still done manually and with a rain sensor circuit that can detect rain as an order to close the front of the booth to protect electronic equipment from rainwater. This system is implemented in an intelligent booth prototype to test whether the algorithm made can overcome the problems experienced by the booth owner.